KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM BELAJAR MENGGUNAKAN STRATEGI TRANSACTIONAL READING INSTRUCTIONAL BERBASIS PROBLEM POSING - Saputri, Linda Dwi; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractReading skills in learning mathematics in schools are rarely taught by teachers. One of the reading strategies is the problem posing-based TRI strategy. Based on the results of research, learning using these strategies can develop students' mathematical communication skills. A comparison of the average value of pretest and posttest is 54 and 73. Precisely the mathematical communication skills of students with visual learning styles after learning with the type of pre solution posing have increased. Of the three subjects, two subjects have increased. Likewise, with students who have kinesthetic learning styles in the same type of the three subjects, two subjects have increased, and one subject has that type. Furthermore, mathematical communication skills of students with visual learning styles after learning with the type within solution posing have increased, of the three subjects, two subjects have increased; as well as students with kinesthetic learning styles in the same type, of the three subjects only one has increased, but there is one subject already able to that type. Then the mathematical communication skills of students with visual learning styles after learning with the type of post solution posing increased in all subjects. Likewise, students with kinesthetic learning styles in the same type, where three subjects have increased.Keywords: Based on Problem Posing, Instructional Transactional Reading Strategy (TRI), Mathematical Communication Strategy